Characteristics and physical properties of poplar woods from Río Negro, Patagonia Argentina - Medina, Andrea Alejandra; Baucis, Agustín G.; Catalán, Mariano A.; Andía, Ismael R.; Trangoni, Federico; Razquin, Milagros; Pampiglioni, Antonela; Vuillermet, Anabella (Instituto de Ecología, A.C., 2018)
Poplar cultivation began in Northern Patagonia, mainly in the Rio Negro province, as windbreaks for the protection of horticultural and fruit crops in its irrigated valleys. At present there are 6000 km of linear length of forest curtains and about 900 ha of poplar plantations in that province. The wood is used chiefly for the manufacture of containers and packaging, and is also used in building, furniture industry, laminated wood (plywood) and cellulose paste. No information is available on the characteristics and properties of these woods, which would be necessary for optimizing its exploitation and maximizing its value for different uses. This study describes macro and microscopic characteristics and physical properties of the wood of three clones widely used in the area, P. nigra cv. thaisiana, P. alba var bolleana y P. x canadensis conti 12, obtained from five individuals for each clone from windbreaks in Allen, Rio Negro Province, Argentine Patagonia. Low density (< 0.40) and macroscopic characteristics of the wood of the three clones determine its quality for lamination, cellulose paste and container and packaging manufacture. They showed medium volumetric contraction (11.82%, 10.32% y 12.15%, respectively) and were placed among partially stable to lightly unstable woods (V: 0.36 - 0.37). High anisotropic indexes (A > 2.3) revealed low dimensional stability, indicating the need for adequate drying processes for its use in windows and linings.